THE IMPORTANCE OF INTEGRATING SKILLS - Mirzayeva Mahbuba Mamajonovna; Sheraliyeva Mo’mina (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Abstract - In this article , skill integration and its importance in English classes are highlighted . Some tips and useful ways are also included. it can be benefical for both teachers and students.